Evaluation of a protective material to prevent abrasions and infections of joints in baby pigs - Schoneweis, D.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Streptococcal and staphylococcal infections increase with increases in central farrowing housing and cause serious losses in young pigs. The baby pig may be affected in many ways, such as growths on the heart valves; pneumonia, and peritonitis; however, infected joints are the most serious problem in many herds. The pigs develop enlarged, crippling joints. Many die and others are stunted. Tentative diagnoses often are erysipelas; however, culture of the joints usually reveals that a strept and/or a staph is involved.
Swine Industry Day 1973 is known as Swine Day, 1973
Keywords: Swine; Baby pigs; Streptococcal; Farrowing; Staphylococcal